2021
DOI: 10.3390/antibiotics10030335
|View full text |Cite
|
Sign up to set email alerts
|

Quantity and Quality of Aquaculture Enrichments Influence Disease Epidemics and Provide Ecological Alternatives to Antibiotics

Abstract: Environmental heterogeneity is a central component influencing the virulence and epidemiology of infectious diseases. The number and distribution of susceptible hosts determines disease transmission opportunities, shifting the epidemiological threshold between the spread and fadeout of a disease. Similarly, the presence and diversity of other hosts, pathogens and environmental microbes, may inhibit or accelerate an epidemic. This has important applied implications in farming environments, where high numbers of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Structural enrichments have been suspected to represent a bacterial reservoir and vectors for pathogens (Tuckey and Smith, 2001). In contrast, a recent study revealed that a beneficial microbial community introduced by the structures may prevent the development of pathogens through competitive phenomenon (Karvonen et al, 2021). Therefore, fish reared in enriched environments could have an increased resistance through an improved immunocompetence.…”
Section: Discussionmentioning
confidence: 99%
“…Structural enrichments have been suspected to represent a bacterial reservoir and vectors for pathogens (Tuckey and Smith, 2001). In contrast, a recent study revealed that a beneficial microbial community introduced by the structures may prevent the development of pathogens through competitive phenomenon (Karvonen et al, 2021). Therefore, fish reared in enriched environments could have an increased resistance through an improved immunocompetence.…”
Section: Discussionmentioning
confidence: 99%
“…One of the biggest challenges to the growth of industrial aquaculture is disease control (Zheng et al, 2020;Karvonen et al, 2021). In this context, the commensal microbiota is important in the innate and adaptive immunity of animals (Vadstein et al, 2018;Sehnal et al, 2021;Huang et al, 2022), whose change in composition can promote or mitigate disease states in hosts (Sehnal et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In India, the expansion of aquaculture into intensive and semi-intensive methods has been accompanied by an increase in production of fish and shellfish due to high stocking densities. However, stressful environmental circumstances encourage the emergence and spread of infectious diseases through variations in virulence and epidemiological factors [10]. Infectious diseases, especially viral diseases are very difficult to be controlled once established within the culture system [11] due to the peculiar environment where pathogens are constantly lurking for an opportunity when the health status of the host is compromised [12].…”
Section: Common Disease Problems In Indian Aquaculturementioning
confidence: 99%